IMPLICATIONS AND CHALLENGES OF IMPLEMENTING NUCLEAR SECURITY STRATEGIES BY MAJOR POWERS IN SOUTH ASIA: A CRITICAL ANALYSIS - Roshan Ara; Farhan Khalid; Abdul Rehman; Ambreen Aman; Rizwan Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
The qualitative study reveals the region of South Asia has become an insecure part of the world politics and game theatre for the big powers like, United States, China, Russia, British and France due to its internal fears and external threats of the proliferation of the nuclear armaments in South Asia. It examines how big powers are actively shaping the region’s security landscape through diplomatic, economic, and military strategies. The divergent and miscalculated American policies towards South Asia increase the hostile environment in the region. The research work provides insights into how the major powers’ interactions impact South Asia’s security environment and the implications for regional and global stability? What are the Core power dynamics at play in nuclear South Asia and the potential consequences for the region and the world politics? The studies explores implication, challenges, application, and operational strategies of the leading international players and the contemporary scenario of global politics particularly after the terrorist incidents of 9/11. The conflict and diversity among the major powers of different regions invited nuclear proliferation, conventional weaponry race, deterrence and future warfare.